Exploiting the means of information technology in committing drug crimes، especially digital ones. In the light of the law against the crimes of information technology in UAE - Al-Hayas, Khawla Musa Abdullah (Journal of Economic, Administrative and Legal Sciences, 2018)
The aim of this article is to investigate the facts and to show the truth about the narcotics in general and the digital and how dangerous and harmful they are، summarize the current scientific knowledge about the newly discovered term and shed light on all its different aspects، and provide scientific conclusions and recommendations on dealing with the phenomenon of digital drugs and addiction. The methodology of the article: The researcher adopted in this article on the method of estrangement and the method of induction in order to come up with a comprehensive article of such topics as we are looking at a problem of very important and dangerous and the adoption of recommendations and circulation prevents young people falling victim to technology and openness. The article concluded with a set of recommendations، the most important of which is the role of governments in modernizing the deterrent laws that prevent the use of these drugs of all kinds، and training special teams to monitor sites that promote this type of drug and work to withhold it. And training sessions and guidance for young people on the impact of electronic drugs.